APPLICATION OF NOTARIAL LEGISLATION TO FOREIGN CITIZENS - Mamajanova Intizar Turdimatovna (Web of Journals Publishing, 2024)
This article deals with the issues of execution of peculiarities of documents intended to be sent abroad. It can be noted that in recent years in our country are economic reforms that stimulate business interest in Uzbekistan on the part of foreign investors, a noticeable increase in the number of notarial acts performed with the participation or in the interests of foreign legal entities
Keywords: notary, international acts, law, legal status, consular conventions, civil capacity, foreign citizens, stateless persons, legal status.